2021
DOI: 10.1002/mgg3.1792
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of uniparental disomy in a clinical trio exome cohort of 2675 patients

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Investigating 214,915 trios, from the 23andMe sequencing dataset, representing a non-clinical general population, the authors found 105 cases of UPD estimating that UPD occurs with an overall prevalence rate of roughly 1 in 2000 births or 0.05% 103 . The frequency of UPDs found in studies that used exome sequencing of patient-parent trios of large clinical populations for all sorts of genetic conditions is higher and oscillates between 0.2 and 0.6% 104 106 . The investigation for UPDs with whole genome sequencing of 164 parent–child trios in a more selected cohort, an Irish cohort with rare disorders, found 3 UPDs a frequency of 1.8% 105 .…”
Section: Discussionmentioning
confidence: 97%
“…Investigating 214,915 trios, from the 23andMe sequencing dataset, representing a non-clinical general population, the authors found 105 cases of UPD estimating that UPD occurs with an overall prevalence rate of roughly 1 in 2000 births or 0.05% 103 . The frequency of UPDs found in studies that used exome sequencing of patient-parent trios of large clinical populations for all sorts of genetic conditions is higher and oscillates between 0.2 and 0.6% 104 106 . The investigation for UPDs with whole genome sequencing of 164 parent–child trios in a more selected cohort, an Irish cohort with rare disorders, found 3 UPDs a frequency of 1.8% 105 .…”
Section: Discussionmentioning
confidence: 97%
“…Investigating 214,915 trios, from the 23andMe sequencing dataset, representing a nonclinical general population, the authors found 105 cases of UPD estimating that UPD occurs with an overall prevalence rate of roughly 1 in 2,000 births or 0,05% [98]. The frequency of UPDs found in studies that used exome sequencing of patient-parent trios of large clinical populations for all sorts of genetic conditions is higher and oscillates between 0,2 and 0,6% [99][100][101]. The investigation for UPDs with whole genome sequencing of 164 parent-child trios in a more selected cohort, an Irish cohort with rare disorders, found 3 UPDs a frequency of 1.8% [100].…”
Section: Lcshsmentioning
confidence: 99%